3D cellular morphometrics of ovule primordium development in Zea mays reveal differential division and growth dynamics specifying megaspore mother cell singleness - Ouedraogo, Inès; Lartaud, Marc; Baroux, Célia; Mosca, Gabriella; Delgado, Luciana; Leblanc, Oliver; Verdeil, Jean-Luc; Conéjéro, Geneviève; Autran, Daphné (Frontiers in Plant Science, 2023)
Differentiation of spore mother cells marks the somatic-to-reproductive transition in higher plants. Spore mother cells are critical for fitness because they differentiate into gametes, leading to fertilization and seed formation. The female spore mother cell is called the megaspore mother cell (MMC), and is specified in the ovule primordium. The number of MMCs varies by species and genetic background, but in most cases, only a single mature MMC enters meiosis to form the embryo sac. Multiple candidate MMC precursor cells have been identified in both rice and Arabidopsis, so variability in MMC number is likely due to conserved early morphogenetic events. In Arabidopsis, the restriction of a single MMC per ovule, or MMC singleness, is determined by ovule geometry. To look for potential conservation of MMC ontogeny and specification mechanisms, we undertook a morphogenetic description of ovule primordia growth at cellular resolution in the model crop maize. We generated a collection of 48 three-dimensional (3D) ovule primordia images for five developmental stages, annotated for 11 cell types. Quantitative analysis of ovule and cell morphological descriptors allowed reconstruction of a plausible developmental trajectory of the MMC and its neighbors. The MMC is specified within a niche of enlarged, homogenous L2 cells, forming a pool of candidate archesporial (MMC progenitor) cells. A prevalent periclinal division of the uppermost central archesporial cell formed the apical MMC and the underlying cell, a presumptive stack cell. The MMC stopped dividing and expanded, acquiring an anisotropic, trapezoidal shape. By contrast, periclinal divisions continued in L2 neighbor cells, resulting in a single central MMC. We propose a model where anisotropic ovule growth in maize drives L2 divisions and MMC elongation, coupling ovule geometry with MMC fate.